Complex analyses of inverted repeats in mitochondrial genomes revealed their importance and variability - Cechová, Jana; Lýsek, Jirí; Bartas, Martin; Brázda, Václav (Bioinformatics (Oxford, England), 2018)
MOTIVATION: The NCBI database contains mitochondrial DNA (mtDNA) genomes from numerous species. We investigated the presence and locations of inverted repeat sequences (IRs) in these mtDNA sequences, which are known to be important for regulating nuclear genomes. RESULTS: IRs were identified in mtDNA in all species. IR lengths and frequencies correlate with evolutionary age and the greatest variability was detected in subgroups of plants and fungi and the lowest variability in mammals. IR presence is non-random and evolutionary favoured. The frequency of IRs generally decreased with IR length, but not for IRs 24 or 30 bp long, which are 1.5 times more abundant. IRs are enriched in sequences from the replication origin, followed by D-loop, stem-loop and miscellaneous sequences, pointing to the importance of IRs in regulatory regions of mitochondrial DNA. AVAILABILITY AND IMPLEMENTATION: Data were produced using Palindrome analyser, freely available on the web at http://bioinformatics.ibp.cz. CONTACT: vaclav@ibp.cz. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Evolution, Molecular; obrácené repetice; genomika; Inverted Repeat Sequences; genom mitochondriální; Sequence Analysis, DNA; Genome, Mitochondrial; sekvenční analýza DNA; Eukaryota; molekulární evoluce; Genomics